Two new Trematode species parasiting in the snake-head fish (Ophiocephalus maculatus) for Vietnam - Ha, Nguyen Van (Academia Journal of Biology, 2015)
Since 1998, in the study on parasitic in freshwater from the Red river delta, 3 parasitic Trematode species (2 adults and 1 juvenile) were recorded. Among them, 2 Trematode species parasiting in the snake-head fish (Ophiocephalus maculatus): Viitellotrema fusipora Guberlet, 1928 (Halipegidae) and Isoparorchis hypselobagri Southwell, 1913 (Isoparorchidae) (adult form) are found for the first time in Vietnam.